"Caracterización morfométrica de la población bovina adaptada a las condiciones ambientales, en la parroquia Zurmi, del cantón Guaizimi, provincia de Zamora Chinchipe" - Salinas Salinas, José Miguel (2017)
A morphometry research of the bovine population was adapted to environmental conditions, in Zurmi Parish, Guaisimi Canton, Zamora Chinchipe Province, Ecuador. To develop this research, 80 cows (UBAs) were assessed, that were selected from ten farms, located in ten districts of this parish. Some features were measured: rump width rear, rump length, width of chest, thoracic length, chest height, neck length, thoracic perimeter, perimeter of the Metacarpus, pastern length, tail length, cephalic index, Pelvic index, body- mass index (IMC), thoracic index, chest-dactyl rate, index thickness on the Shank. Milk capacity: Dactyl-costal index. Meat processing capacity: transverse pelvic index, longitudinal pelvic index. The obtained data was processed with the statistical program SAS. It was found a variation in the length of rump (p=0,044) and thoracic perimeter with a tendency to vary (p=0,058), in which were found significant differences according to the body conditions of the animals when evaluating measures and zoometric index in bovine females of different ages which were adapted to the environment with different phaneroptical characteristic and without a defined breed group in Zurmi Parish. It was concluded that: They are animals which body length, chest and height average have good strength, with a narrow croup, height and low thoracic perimeter and whose average length is positively correlated with their body condition. Also, that according to the values of the index it can be concluded that the population of cows in this area presents a trend of dual purpose with increased susceptibility to milk production. Key words: Bovine adapted, humid tropics, variance and body conditions.